2015 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE) 2015
DOI: 10.1109/fuzz-ieee.2015.7337884
|View full text |Cite
|
Sign up to set email alerts
|

Item response theory with fuzzy markup language for parameter estimation and validation

Abstract: Owing to advanced technical progress in information and communication technology, computerized adaptive assessment becomes more and more important for the personalized learning achievement. According to the response data from the conventional test and three-parameter logistic (3PL) model of the item response theory (IRT), this paper combines IRT with fuzzy markup language (FML) for an adaptive assessment application. The novel FML-based IRT estimation mechanism includes a Gauss-Seidel (GS) parameter estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…After defining an items' parameters, we adopt the maximum a posteriori estimation approach to estimate a student's ability 𝜃 ̂ based on their response pattern u to items 1, 2, 3, …, and |I| [20]. By contrast, when the items parameters are unknown, the IRTBE mechanism can estimate them according to the examinees' abilities [29]. The inputs of IRTBE are items 1, 2, 3, ..., and |I| and the response pattern u = (u1, u2, …, u|I|) for a student.…”
Section: B Test Information Test Standard Error and Irt-based Bayesia...mentioning
confidence: 99%
See 2 more Smart Citations
“…After defining an items' parameters, we adopt the maximum a posteriori estimation approach to estimate a student's ability 𝜃 ̂ based on their response pattern u to items 1, 2, 3, …, and |I| [20]. By contrast, when the items parameters are unknown, the IRTBE mechanism can estimate them according to the examinees' abilities [29]. The inputs of IRTBE are items 1, 2, 3, ..., and |I| and the response pattern u = (u1, u2, …, u|I|) for a student.…”
Section: B Test Information Test Standard Error and Irt-based Bayesia...mentioning
confidence: 99%
“…We define the possibility of correctly answering the item as the output fuzzy variable Correct_Response_Possibility (CRP). Next, we briefly describe how to construct the knowledge base and rule base of the FML-based dynamic assessment mechanism [29].…”
Section: B Fml-based Dynamic Assessment Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies focused on the field of assessment have suggested promoting greater efforts and strategies that demonstrate the effectiveness of learning in continuous assessment/formative assessment processes supported by technology (7)(8)(9)(10)(11). The literature contains proposals in specific domains (12)(13)(14)(15)(16). These do not consider contextual entities that allow capturing the characteristics or situations of each student, limiting possible adjustments or improvements to the assessment conditions and educational practices established by the teacher.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%